Gender in Play on the Shakespearean Stage : Boy Heroines and Female Pages - Shapiro, Michael, 1938- (Book collections on Project MUSE., 1996)
"Like other English Renaissance writers and dramatists, Shakespeare was attracted to the heroine in male disguise. Gender in Play on the Shakespearean Stage examines the use of this type of character--man playing woman playing man--by framing five plays by Shakespeare against readings of some of the other "female page" plays written by other playwrights of the period. The many variations Michael Shapiro traces are placed in the context of female cross-dressing as a social phenomenon and in the context of female impersonation as the standard way of representing women on the Shakespearean stage. Shakespeare's use of the female page spanned his entire career: The Two Gentlemen of Verona (an early comedy), The Merchant of Venice, As You Like It, Twelfth Night (mature romantic comedies), and Cymbeline (a late romance). Shapiro deploys several modes of literary criticism to establish the distinctiveness of each of Shakespeare's five disguised heroine plays and to trace the subtle and ingenious variations on the motif by such writers as Greene, Fletcher, Chapman, Middleton, Jonson, and Ford. The popularity of the "female page" is examined as a playful literary and theatrical way of confronting, avoiding, or merely exploiting issues such as the place of women in a patriarchal culture and the representation of women on stage. Looking beyond and behind the stage for the cultural anxieties that cross-dressing London women being punished as prostitutes and speculation that the apprentices who played female roles in adult companies engaged in homoerotic practices. [This book] will appeal not only to scholars of Renaissance drama but to any reader interested in the historical construction and analysis of gender and sexuality, both on- and offstage"-- Back cover.